Sustainable green synthesis of CoFe2O4/TiO2 magnetic nanocomposites using Parkia speciosa (stinky bean) peel extract as an electrocatalyst for hydrogen production - Putri Aulia, Syafhira; Nadia, Aida; Annas, Dicky; Marlinda, Lenny; Jihad Madiabu, Mohammad; Lotebulo Ndruru, Sun Theo Constan; Marlina, Anita; Khoiriah, Khoiriah; Sisca, Vivi; ‘Adany, Fildzah; Kurnia Amin, Amalia; Al Muttaqii, Muhammad; et al. (Vacuum, 2025)
The green synthesis of metallic nanocomposites through the alloying of transition metals offers a promising pathway to address the high costs and scarcity of noble metals in hydrogen production electrocatalysis (HPE). This study introduces a simple, eco-friendly synthesis method for producing CoFe2O4/TiO2 magnetic nanocomposites (CoFe2O4/TiO2 MNCs), using stinky bean peel extract as a natural hydrolyzing and capping agent. The successful synthesis of CoFe2O4/TiO2 MNCs was confirmed through a range of characterization techniques, including X-ray diffraction (XRD), vibrating sample magnetometry (VSM), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, ultraviolet–visible diffuse reflectance spectroscopy (UV–Vis DRS), X-ray photoelectron spectroscopy (XPS), Brunauer-Emmet-Teller (BET), and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDX). Selected area electron diffraction (SAED) and transmission electron microscopy (TEM) were also employed, with TEM revealing an average particle size of 17.33 nm. The electrocatalytic performance of the CoFe2O4/TiO2 MNCs was evaluated using cyclic voltammetry (CV) and linear sweep voltammetry (LSV). Results indicated optimal catalytic properties, marked by the lowest overpotential, highest current density, lowest Tafel slope, and highest double-layer capacitance, underscoring the potential of these nanocomposites as effective electrocatalysts for hydrogen production. In summary, these findings position CoFe2O4/TiO2 MNCs as a promising, cost-effective alternative for fabricating electrocatalysts in hydrogen production applications, leveraging green synthesis methods for a more sustainable approach to energy technolog
Keywords: Green synthesis; CoFe2O4/TiO2 magnetic nanocomposites; Electrocatalyst; Hydrogen production